Systematic analytical QC for process GC - McCown, Mick (Knovel, 2011)
Analytical quality control is the set of processes and procedures designed to produce and ensure a reliable measurement from an analytical system. The purposes of analytical quality control (as opposed to process quality control) are to demonstrate the successful performance of the analytical system (in the short term, a process known either as validation or bench-marking), and to gather the data that will allow prediction of the need for non-routine maintenance (in the long term).
Keywords: Chromatographic analysis.; Quality control.; elektronické knihy; electronic books